Antibiotics and antimicrobial resistance: Evaluation of the knowledge, attitude, and perception among students and faculty within US dental schools. Issue 3 (12th October 2020) - Holz, Magdalena; Naavaal, Shillpa; Stilianoudakis, Sprio; Carrico, Caroline; Byrne, B. Ellen; Myers, Garry L.
Abstract: Purpose: This study examined knowledge, attitudes, perceptions, and awareness regarding antibiotic use among students and academic faculty in US dental schools. Methods: Two questionnaires, 1 for third‐year/fourth‐year dental students and the other for academic deans/department chairs were administered electronically. Questions on demographics, antibiotic knowledge, educational formats, and the role of dentistry in antibiotic stewardship were included. Knowledge about antibiotics and antibiotics stewardship was compared between third‐year and fourth‐year students and between students and academic faculty using t‐test and chi‐squared test at 0.05 significance level. Results: A total of 18 responses on the academic dean and department chair survey and 172 responses on the dental student survey were collected. Overall, 71% of students reported that they could benefit from more education regarding antibiotics. Both faculty and students agreed that dentistry should play an important role in reducing antimicrobial resistance, but most dental students were "not at all familiar" with the term antimicrobial stewardship and several (32%) were unsure if clinical guidelines were present at their schools. Conclusion: Improvements to the dental educational curriculum regarding the responsible use of antibiotics, along with the implementation of stewardship programs within dentistry are strongly encouraged.